Mixed Lubrication Analysis of Vane Sliding Surface in Rotary Compressor Mechanisms - Yasutaka Ito (Japanese Society of Tribologists, 2007)
Numerical analysis for mixed lubrication has been performed in order to investigate the lubrication characteristics of the sliding surface of the vane in a rotary compressor. The modified Reynolds equation and the elastic contact equation, considering the surface roughness, are solved as a coupled problem. Using this analysis, the lubrication characteristics of the sliding surface of the vane are investigated by parameter survey on the design parameters such as the vane-slot length and the clearance between the vane and vane-slot. It is found that the influences of the vane-slot length on the friction loss were larger than that of the clearance.